Influence of Digital Transformations and Operational Efficiency on the Perceived Profitability of Citilink Indonesia: Customer Satisfaction as a Mediating Variable - Sutarto Wisnu Wardana; MN Nuryasman; Faizul Mubarok (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to examine the influence of digital transformation and operational efficiency on airline profitability, with customer satisfaction as a mediating variable. Methodology: A quantitative approach was employed using data collected from 360 passengers of Citilink Indonesia at Soekarno-Hatta International Airport. Data were analyzed using SEM-PLS with SmartPLS 4.0 software. Results: Digital transformation has a significant positive effect on both customer satisfaction and profitability. Operational efficiency positively influences customer satisfaction and profitability. Customer satisfaction partially mediates both relationships. Findings: Digital transformation and operational efficiency both independently and jointly improve airline profitability through direct effects and via the mediating mechanism of customer satisfaction. Novelty: This study provides an integrated empirical model linking digital transformation, operational efficiency, customer satisfaction, and profitability in the Indonesian low-cost carrier context, a segment underrepresented in international management literature. Originality: The study validates a four-construct model integrating digital transformation, operational efficiency, customer satisfaction, and profitability in Indonesian aviation, identifying partial mediation mechanisms not previously specified in the literature. Conclusion: Digital transformation and operational efficiency significantly improve airline profitability both directly and indirectly through customer satisfaction. Airlines should align digital innovation and operational excellence with customer-centric strategies to achieve sustainable competitive advantage. Type of Paper: Research Article.